Kajian Pemeriksaan Kondisi Jembatan di Ruas Jalan Nasional Provinsi Jambi (Studi kasus: Jembatan Rangka) - Handayani, Elvira; Nuklirullah, M.; Saputra, Wahyu (Jurnal Civronlit Unbari, 2024)
Bridge inspection is one of the most important parts in a bridge management information system. Bridge inspection is related to bridge requirements, planning for maintenance or service improvement in the future. This study discusses the framework of bridges on several bridges which are stretched on Jambi provincial roads, specifically the Sei Bridge. Bernai, Lubuk Kuari and Sei Bridge. Trap Expected more than 25 years. The examination in this study only waits for the detailed inspection of the manual issued by the public works department. This study uses the calculation method proposed in the BMS (Bridge Management System) which has been translated into SMJ (Bridge Management System) based on conditions that occur in the field. The results of the bridge situation examination obtained from this study are Sei. Trapping has a condition value of 1, Lubuk Kuari has a condition value of 2, Sei. Bernai has a condition value of 1.